Balanced Mix Design and Benchmarking: A Case Study in Establishing Performance Test Thresholds. Issue 12 (December 2022) - Bowers, Benjamin F.; Diefenderfer, Stacey D.; Moore, Nathan; Lynn, Tiana
A balanced mix design (BMD) approach for asphalt mixtures incorporates laboratory performance tests into the mix design acceptance process. However, test selection and subsequent performance thresholds must be selected, which is no easy endeavor when considering the number of promising tests and the variation in asphalt mix designs and components between states or regions. While the Virginia Department of Transportation's (VDOT) BMD specification has been circulated for multiple years now, this article presents the approach taken by VDOT to investigate the various tests, considerations taken in selecting tests, and the establishment of performance thresholds. Data and discussion of six different performance tests encompassing durability, rutting, and cracking for 11 common Virginia mixes are presented. The performance threshold selection process is outlined. Further considerations in the final test selection process are discussed. In conclusion, the initial draft specification for BMD is provided.